2021
DOI: 10.1017/flo.2021.9
|View full text |Cite
|
Sign up to set email alerts
|

Solidity effects on the performance of vertical-axis wind turbines

Abstract: The variety of configurations for vertical-axis wind turbines (VAWTs) make the development of universal scaling relationships for even basic performance parameters difficult. Rotor geometry changes can be characterized using the concept of solidity, defined as the ratio of solid rotor area to the swept area. However, few studies have explored the effect of this parameter at full-scale conditions due to the challenge of matching both the non-dimensional rotational rate (or tip speed ratio) and scale (or Reynold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…High fidelity laboratory and numerical experiments with porous plates and wind turbines indicated that the proposed correction performs equally as well as conventional ones in low-solidity regimes, but becomes more accurate as the solidity/induction factor increases. The applicability of the current model might be somewhat limited in conventional horizontal axis wind turbines, as they tend to operate in low-solidity regimes, but might become especially relevant when considering blockage effects in high-solidity configurations such as many-bladed vertical axis wind turbines, tidal turbines, and more generally bluff bodies of arbitrary porosity, including the fully solid limit in which splitter plates are used to suppress vortex shedding, and where no blockage correction model is currently available (see, for instance, Apelt & West 1975;Chapman et al 2013;Miller et al 2021). effect of the vena contracta is negligible.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…High fidelity laboratory and numerical experiments with porous plates and wind turbines indicated that the proposed correction performs equally as well as conventional ones in low-solidity regimes, but becomes more accurate as the solidity/induction factor increases. The applicability of the current model might be somewhat limited in conventional horizontal axis wind turbines, as they tend to operate in low-solidity regimes, but might become especially relevant when considering blockage effects in high-solidity configurations such as many-bladed vertical axis wind turbines, tidal turbines, and more generally bluff bodies of arbitrary porosity, including the fully solid limit in which splitter plates are used to suppress vortex shedding, and where no blockage correction model is currently available (see, for instance, Apelt & West 1975;Chapman et al 2013;Miller et al 2021). effect of the vena contracta is negligible.…”
Section: Discussionmentioning
confidence: 99%
“…The above prediction is identical to the one obtained using the Rankine-Froude theory (Hansen 2015), which constitutes the basis of most blockage correction models for porous plates and wind turbines. Figure 1 shows the well-known failure of the Rankine-Froude-Taylor theory when porosity becomes small, which limits the applicability of blockage correction models to high-porosity regimes (Apelt & West 1975;Ross & Polagye 2020a;Miller et al 2021). Appendix A presents a relation that connects u * with β = A p /A (where A p and A are the porous and gross areas of the plate, respectively), proposed by Taylor & Davies (1944).…”
Section: Unconfined Platementioning
confidence: 99%
See 3 more Smart Citations